1987
DOI: 10.1111/j.1528-1157.1987.tb03683.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Focal Abnormalities of Neuroimaging Studies During Focal Status Epilepticus

Abstract: We report transient changes in computed tomography (CT) and magnetic resonance imaging (MRI) scans in a patient with focal status epilepticus, referred to us with a tentative diagnosis of neoplasm based on CT and angiographic findings. EEG seizures originated independently from each temporal-occipital area, predominantly from the right. Previous EEGs had shown almost exclusively right temporo-occipital epileptogenic activity. MRI showed increased signal intensity, and CT showed decreased right hemisphere atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 10 publications
4
63
0
2
Order By: Relevance
“…Increased oxygen consumption in the cortical epileptogenic zone and the resulting hypoxia are assumed to lead to an accumulation of CO 2 and lactic acid, which in turn causes vasodilation, loss of autoregulation, and increased cerebral blood flow. 13,17) Such neuroradiological findings mentioned above were similar to those of the present case, but no EEG findings to support the diagnosis of epilepsy were obtained. EEG findings of status epilepticus may be normal when the epileptic focus is small 11) or deep in the brain structure.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Increased oxygen consumption in the cortical epileptogenic zone and the resulting hypoxia are assumed to lead to an accumulation of CO 2 and lactic acid, which in turn causes vasodilation, loss of autoregulation, and increased cerebral blood flow. 13,17) Such neuroradiological findings mentioned above were similar to those of the present case, but no EEG findings to support the diagnosis of epilepsy were obtained. EEG findings of status epilepticus may be normal when the epileptic focus is small 11) or deep in the brain structure.…”
Section: Discussionsupporting
confidence: 73%
“…11,16,32) Neuroimaging signs of transient abnormalities in patients with status epilepticus characteristically involve a focal area either in the white matter or in the combined white and gray matter, appearing as low density areas by CT, and as decreased signal intensity on T 1 -weighted images and/or increased signal intensity on T 2 -weighted ones by MR imaging, without a mass effect. 9,13,31) Such changes are thought to be due to vasogenic edema induced by hyperemia. Increased oxygen consumption in the cortical epileptogenic zone and the resulting hypoxia are assumed to lead to an accumulation of CO 2 and lactic acid, which in turn causes vasodilation, loss of autoregulation, and increased cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many observations in epilepsy patients (19)(20)(21)(22)(23)(24), confirmed by animal studies (25)(26)(27)(28), demonstrated that SE provokes transient BBB breakdown and vasogenic edema in the area of the seizure focus. It is commonly proposed that local (relative hypoxia secondary to increased ictal metabolism with an increase in local PCO 2 and lactate) and systemic (increase in blood pressure and decrease in blood pH) physiologic changes induce a vasodilatation, resulting in increased regional blood flow and BBB breakdown (25,26,29).…”
Section: Role Of the Bbb Breakdown In The Genesis Of The Lesionsmentioning
confidence: 75%
“…The above-mentioned metabolic phenomena are proportional to the frequency and duration of the seizures 1,11,12 . They determine a transitory alteration of the BBB, an increased of vascular permeability and the subsequent appearance of cerebral edema.…”
Section: Discussionmentioning
confidence: 99%